Case Report: Pelvic abscess formation secondary to the use of commercial hemostatic topical agent in an immunocompromised patient? - Mónica Monzón-Vargas; Yuliana Gómez- Meraz; Rodrigo Ayala-Yáñez (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2017)
Various hemostatic agents are currently available for routine laparoscopic procedures, avoiding thermal lesions due to energy devices and the complexity of intracorporeal sutures, however, evidence of complications in immunocompromised patients is still lacking. We present the case of a severely immunocompromised gynecological patient who underwent a routine laparoscopic cystectomy, where a local hemostatic agent was employed; further complications arose, a second diagnostic laparoscopy revealed a pelvic abscess with severe adhesion formation. All under a complicated clinical setting due to an impaired immune response, whether this abscess was caused due to the hemostatic agent or other patient's conditions remains to be determined, still, various clinical factors and patient's response need to be taken into account as the cause of the abscess formation.